2008
DOI: 10.1007/s00221-008-1307-y
|View full text |Cite
|
Sign up to set email alerts
|

Monkey primary somatosensory cortical activity during the early reaction time period differs with cues that guide movements

Abstract: Vibration-related neurons in monkey primary somatosensory cortex (SI) discharge rhythmically when vibratory stimuli are presented. It remains unclear how functional information carried by vibratory inputs is coded in rhythmic neuronal activity. In the present study, we compared neuronal activity during wrist movements in response to two sets of cues. In the first, movements were guided by vibratory cue only (VIB trials). In the second, movements were guided by simultaneous presentation of both vibratory and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Under this assumption, motor control of orofacial movements during speech and of digits during fine manipulation would be dependent on continuous monitoring of superficial and deep mechanoreceptive sensory input. Single-neuron recordings in behaving monkeys have shown that the primary somatosensory area in particular may indeed play an important role in orofacial (Lin et al, 1994; Sessle et al, 2005) and hand/digit motor control (Liu et al, 2008; Gardner et al, 2007; Salimi et al, 1999; Wannier et al, 1991). Whereas the transient tactile inputs to the digits during active exploration or manipulation of small objects likely require fast integration over brief temporal intervals, tactile input to the lips associated with orofacial behaviors repeats and must be eventually maintained and integrated in primary sensory cortices or higher order cortical areas over slightly longer intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Under this assumption, motor control of orofacial movements during speech and of digits during fine manipulation would be dependent on continuous monitoring of superficial and deep mechanoreceptive sensory input. Single-neuron recordings in behaving monkeys have shown that the primary somatosensory area in particular may indeed play an important role in orofacial (Lin et al, 1994; Sessle et al, 2005) and hand/digit motor control (Liu et al, 2008; Gardner et al, 2007; Salimi et al, 1999; Wannier et al, 1991). Whereas the transient tactile inputs to the digits during active exploration or manipulation of small objects likely require fast integration over brief temporal intervals, tactile input to the lips associated with orofacial behaviors repeats and must be eventually maintained and integrated in primary sensory cortices or higher order cortical areas over slightly longer intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Two adult male rhesus monkeys ( Macaca mulatta : E, N) were trained to make wrist flexion and extension movements in response to vibratory or visual go-cues (Lebedev and Nelson, 1995 , 1999 ; Liu et al, 2008 ). The monkeys were cared for in accordance with the National Research Council Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Once an animal reached a stable daily performance level (∼2000 rewarded trials per experimental session), it was prepared for recording. A stainless steel recording chamber was surgically implanted over the skull to allow for extracellular recordings of the activity of basal ganglia neurons by using platinum–iridium microelectrodes with impedances of 1–2 MΩ (see Gardiner and Nelson, 1992 ; Liu et al, 2008 ). Transdural penetrations began no sooner than 1 week after the chamber implantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocols were approved by the Animal Care and Use Committee of The University of Tennessee Health Science Center, Memphis. Detailed descriptions of the experimental apparatus have been provided elsewhere (Gardiner and Nelson, 1992 ; Lebedev and Nelson, 1995 ; Liu et al, 2005 , 2008 ). A brief description is provided below.…”
Section: Methodsmentioning
confidence: 99%